16 Emergency department patients with suicide risk: impact of alcohol intoxication. (19th September 2017) - Urban, Chantel; Betz, Marian E; Arias, Sarah A; Segal, Daniel L; Miller, Ivan; Camargo, Carlos A; Boudreaux, Edwin D
Abstract : Statement of purpose: To identify care differences between those with and without alcohol intoxication among emergency department (ED) patients who screened positive for suicide risk. Methods: This was a retrospective, observational study of electronic medical records at an urban ED with universal suicide risk screening. Eligible patients had screened positive ('active suicide ideation' or 'suicide attempt within past 6 months') between January 2014 and December 2015. We reviewed a random sample of charts from three a priori age groups (18–34 years, n=300; 35–59 years, n=300; and 60+years, n=200) for demographic, medical, and visit characteristics. The primary outcomes were evaluation by a mental health professional, provision of resources, and ED disposition. Results: Suicidal individuals who were intoxicated (blood alcohol level >0 or other intoxication documentation) were more often males aged 35–59 years. Intoxicated, suicidal individuals were less likely than those who were not intoxicated to see a mental health professional during the ED visit (72% vs 84%, p<0.0001), or be admitted/transferred to a psychiatric or substance abuse facility (21% vs 30%, p-value<0.0001). Intoxicated individuals were more likely to be discharged home (68% vs 59%, p-value<0.0001) and receive referral resources (63% to 56%, p<0.0001). Conclusion: There were discrepancies in ED care between intoxicated and non-intoxicated patients. This may relate to patients who express suicidality while intoxicated and recant once sober, leading to a less thorough evaluation. It may also reflect difficulty engaging patients in mental health care while intoxicated. Significance: Alcohol intoxication is a risk factor for suicide, yet it can complicate risk assessment by impairing patients' judgement and thinking. While guidelines recommend suicidal ED patients receive a comprehensive risk assessment, this may not always occur. ED providers may need additional education or guidelines to enhance best practice for these cases.